Strategi Pemberdayaan Yang Dilakukan Oleh Komunitas WEPOSE (We Different But One Purpose) Terhadap Anak Jalanan Bantaran Rel Wonokromo Melalui Pendampingan Pendidikan - Virdiansyah, Erlang; Arundinasari, Indira (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2025)
This research aims to analyze the empowerment strategies for street children conducted by the WEPOSE community in Surabaya City, focusing on educational mentoring as a means to improve the quality of life of street children along the Wonokromo railway tracks. Indonesia, as a developing country, faces complex challenges regarding the existence of street children caused by poor family economic conditions and surrounding environmental influences. Street children face marginalization, high risk levels, and exploitation with limited access to education and health services. This research employs a qualitative descriptive method with a participant observation approach at WEPOSE's main headquarters and its assisted areas, covering 336 street children in five strategic locations. The analytical framework uses Suharto's "5P" community empowerment strategy theory, which includes enabling, strengthening, protecting, supporting, and maintaining. Data collection techniques were conducted through unstructured interviews, documentation, and participant observation with purposively selected informants. Data analysis uses the Miles, Huberman, and Saldana model through stages of collection, condensation, narrative data presentation, and conclusion drawing. Data validity was tested using source triangulation to ensure the credibility of findings. The research results are expected to contribute to the development of an effective community-based empowerment model for addressing street children problems in urban areas through innovative and sustainable educational approaches